Repositioning Australian cities as settings for memorable nature-based experiences aimed at Chinese tourists. Issue 3 (1st September 2016) - Weiler, Betty; Chen, Hanyu
ABSTRACT: The package tourists dominate the outbound Chinese holiday travel market, and to date their nature tourism experiences have been investigated, analysed and reported primarily with a Western gaze. This paper critically examines the findings of previous studies from both Chinese and English-language literature, to develop a more nuanced understanding of the values, perceptions and expectations underpinning what Chinese visitors consider a beautiful natural environment. Marrying this with an understanding of the constraints and opportunities of Chinese visitors to Australia provides fresh insights regarding appropriate strategies for delivering memorable nature-based experiences. These are presented in the form of a typology of nature-based experiences in urban environments that, if examined through a Chinese cultural lens, may help diversify and deepen opportunities for memorable experiences for the Chinese market. To reposition cities in Australia and elsewhere as settings for memorable nature-based experiences for Chinese visitors, key contexts, requirements and components of each experience type are outlined. Implications are discussed for the current package tour market as well as the growing independent travel market which, although largely unresearched, appears to share some of the same values, perceptions, constraints and expectations in terms of nature-based experiences.